The Aboodh transformation-based homotopy perturbation method: new hope for fractional calculus - Tao, Huiqiang; Anjum, Naveed; Yang, Yong-Ju (Frontiers in Physics, 2023)
The fractional differential equations can also model various complex problems in physics and engineering, and there is no universal method to solve the fractional models precisely. This paper offers a new hope for this purpose by coupling the homotopy perturbation method with Aboodh transform. The new hybrid technique leads to a simple approach to finding an approximate solution, which converges fast to the exact one with less computing effort. An example of the fractional casting-mold system is given to elucidate the hope for fractional calculus, and this paper serves as a model for other fractional differential equations.